Olahan Singkong Di Desa Raba Wawo Menjadi Kripik SIDEWA (Kripik Singkong Desa Wawo) - Intisari sari; aris munandar (Jurnal Pengabdian Kepada Masyarakat Ceria (JPKMC), 2023)
Agricultural produce in the form of cassava which is abundant in Raba village has not been able to increase the income of farmers, so far cassava yields have only been used as additional food ingredients, and some traditional preparations for sale. This condition is due to the lack of understanding and skills of residents in processing cassava which has a higher selling value. This condition became aware that community service activities (PKM) were carried out with the aim of empowering the Raba village community in processing cassava as the basic ingredient for making cassava chips. This activity The method in this activity begins with initial preparation, implementation and final evaluation. The results of empowerment activities include 1) increasing partners' understanding of cassava processing, 2) forming partner skills, 3) products in the form of ready-to-sell packaged cassava chips, and 4) forming new business units in household-based cassava management and processing. Activities still need continuous assistance so that partners can truly be independent in the management and processing of cassava into flour products that are hygienic and have a halal certificate.